Актуалізація моральнісних основ в політиці - Колядко, Б. С.; Колядко, Б. С.; Koljadko, B. (My University, 2013)
The article deals with one of the urgent problems in contemporary political life – namely, the study of the mechanism of interaction of concepts «politics» and «morality». The essence of these concepts is defined as well as their differences? time of emergence and similarities are clarified. Possibilities of the study of the mechanism of interaction of politics, law and morality in modern Ukrainian political process are outlined.
Колядко Б. С. Актуалізація моральнісних основ в політиці / Б. С. Колядко // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 275-283.
Keywords: взаємодія моралі і політики; сутність політики; сутність моралі; час виникнення політики і моралі; взаимодействие морали и политики; сущность политики; сущность морали; время возникновения политики и морали; interaction of morality and politics; the essence of politics; the essence of morality; time of occurrence of politics and morality